Yield reduction caused by elevated temperatures and high nitrogen fertilization is mitigated by SP6A overexpression in potato (Solanum tuberosum L.) - Koch, Lisa; Lehretz, Günter; Sonnewald, Uwe; Sonnewald, Sophia (Plant Journal, 2024)
Potatoes (Solanum tuberosum L.) are a fundamental staple for millions of people worldwide. They provide essential amino acids, vitamins, and starch – a vital component of the human diet, providing energy and serving as a source of fiber. Unfortunately, global warming is posing a severe threat to this crop, leading to significant yield losses, and thereby endangering global food security. Industrial agriculture traditionally relies on excessive nitrogen (N) fertilization to boost yields. However, it remains uncertain whether this is effective in combating heat-related yield losses of potato. Therefore, our study aimed to investigate the combinatory effects of heat stress and N fertilization on potato tuber formation. We demonstrate that N levels and heat significantly impact tuber development. The combination of high N and heat delays tuberization, while N deficiency initiates early tuberization, likely through starvation-induced signals, independent of SELF-PRUNING 6A (SP6A), a critical regulator of tuberization. We also found that high N levels in combination with heat reduce tuber yield rather than improve it. However, our study revealed that SP6A overexpression can promote tuberization under these inhibiting conditions. By utilizing the excess of N for accumulating tuber biomass, SP6A overexpressing plants exhibit a shift in biomass distribution towards the tubers. This results in an increased yield compared to wild-type plants. Our results highlight the role of SP6A overexpression as a viable strategy for ensuring stable potato yields in the face of global warming. As such, our findings provide insights into the complex factors impacting potato crop productivity.
CRIS-Team Scopus Importer:2024-02-23
Keywords: combined stress; fertilization; heat stress; nitrogen; potato; SP6A; tuberization; yield